Comparison of Shoulder Kinematics and Muscle Activation of Female Elite Handball Players With and Without Pain—An Explorative Cross-Sectional Study - Torabi, Tina Piil; Juul-Kristensen, Birgit; Dam, Mogens; Zebis, Mette K.; van den Tillaar, Roland; Bencke, Jesper (Frontiers in Sports and Active Living, 2022)
Non-traumatic shoulder injuries are common in team handball. However, many athletes continue to throw, despite pain in the shoulder. This study investigated upper body kinematics and muscle activation while throwing in female elite handball players with and without shoulder pain. Thirty female elite team handball players, 15 with pain (age 22.2 ± 2.9 yrs.) and 15 without pain (age 20.4 ± 2.6 yrs.) performed five standing throws in which joint kinematics and muscle activity were measured in the following muscles: pectoralis major, infraspinatus, serratus anterior, latissimus dorsi, and upper-, middle-, and lower trapezius. The main findings revealed that peak joint angles and angular velocities were not different between groups; however, group differences were observed in earlier timing of position and longer time spent in maximal shoulder extension and external shoulder rotation in the pain group compared with the no pain group. The pain group also revealed a significant lower muscle peak activity in the serratus anterior during the cocking phase compared to the no pain group. After the cocking phase and at ball release, the groups had similar activation. In conclusion, the present study showed group differences in appearance and time spent in maximal humerus extension and external rotation and a different serratus anterior muscle peak activity between elite handball players playing with and without shoulder pain, which are identified as possible mechanisms of adaptation to avoid pain.